Interpretasi Kaidah Arsitektur Islam Pada Desain Rumah Tradisional Aceh - Astrid Annisa; Mufti Ali Nasution (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Aceh, as a province deeply rooted in Islamic Sharia, consistently applies the teachings of Islam in every aspect of community life. Aceh has customs and culture based on Islamic teachings. Traditional Acehnese houses, commonly known as 'Rumoh Aceh,' represent the traditional homes of the Acehnese people, conveying meanings and philosophies related to the culture and customs of the Acehnese community. This research aims to identify and examine the compatibility of traditional Acehnese house designs based on Islamic values and architectural principles.